2020
DOI: 10.1101/2020.01.24.919175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single generation exposure to a captive diet: a primer for domestication selection in a salmonid fish?

Abstract: 14Millions of wild animals in captivity are reared on diets that differ in their uptake and composition 15 from natural conditions. Few studies have investigated whether such novel diets elicit 16 unintentional domestication selection in captive rearing and supplementation programs. In highly 17 fecund salmonid fishes, natural and captive mortality is highest in the first few months of 18 exogenous feeding. This high early mortality might be a potent driver of unintentional selection 19 because wild fish norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The hatchery environment is expected to favor individuals with a fast metabolic rate (Robertsen et al, 2019). However, because metabolic rate measurements can induce stress responses (Murray et al., 2017) and domestication‐related phenotypic changes can be evident in hatchery environments already after a single generation in salmonids (Christie et al., 2016; Islam et al., 2020), the result could be explained by a better ability of the hatchery‐population fish to adjust to handling during metabolic rate measurements. Further, metabolic rate might relate to the life‐history strategy of the fish (Rosenfeld et al., 2015), as the wild fish represented resident and the captive fish migratory brown trout forms (Lemopoulos et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hatchery environment is expected to favor individuals with a fast metabolic rate (Robertsen et al, 2019). However, because metabolic rate measurements can induce stress responses (Murray et al., 2017) and domestication‐related phenotypic changes can be evident in hatchery environments already after a single generation in salmonids (Christie et al., 2016; Islam et al., 2020), the result could be explained by a better ability of the hatchery‐population fish to adjust to handling during metabolic rate measurements. Further, metabolic rate might relate to the life‐history strategy of the fish (Rosenfeld et al., 2015), as the wild fish represented resident and the captive fish migratory brown trout forms (Lemopoulos et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The hatchery environment is expected to favor individuals with a fast metabolic rate (Reid et al 2012;Robertsen et al 2018). However, because metabolic rate measurements can induce stress responses (Murray et al 2017) and domestication-related phenotypic changes can be evident in hatchery environments already after a single generation in salmonids (Christie et al 2016, Islam et al 2020, the result could be explained by a better ability of the hatchery-population fish to adjust to handling during metabolic rate measurements. Further, metabolic rate might relate to the life-history strategy of the fish (Rosenfeld et al 2015), as the wild fish represented resident and the captive fish migratory brown trout forms (Lemopoulos et al 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Live prey and/or dry feed were provided consistently to ensure that fish were not food limited, there were no predators or competitors, and water quality was always managed properly. Studies have shown that cultured fish grew significantly faster than their wild counterparts due to stable food availability and quality, higher consumption rates, less exercise and energy expenditure (Islam et al., 2020; Teletchea, 2019; Wringe et al., 2016). Other researchers have also shown that many other factors can influence fecundity, such as environmental conditions (Salvanes & Braithwaite, 2005), stress (Schreck et al., 2001), fish size (Kjesbu et al., 1996) and the duration of the spawning period (Bennett, 2005; Brown et al., 2013; Hunter et al., 1985).…”
Section: Discussionmentioning
confidence: 99%